Evaluation of the moulding process for production of short-fibre-reinforced C/C-SiC composites. Issue 4 (April 2020) - Nier, Natalia; Päßler, Erik; Weißhuhn, Julia; Roder, Kristina; Nestler, Daisy; Kroll, Lothar; Spange, Stefan; Wagner, Guntram
Abstract: For the production of C/C-SiC brake discs via the liquid silicon infiltration method (LSI), the hot pressing process is the state of art technique for the moulding of the CFRP composites. This technique consists of several manual steps which increase production cost. The overall cost can be reduced by implementing injection moulding process. In this paper the influence of the moulding process (hot pressing, injection moulding) on the properties of semi-finished and final products during the production of short-fibre-reinforced C/C-SiC composites by means of the LSI process are examined. The starting polymer is chemically characterised. Carbon-fibre-reinforced plastic (CFRP) composites are fabricated by hot pressing, as well as injection moulding process. The CFRP composites are converted into porous C/C composites by pyrolysis. Liquid silicon is infiltrated to form dense C/C-SiC composites, which are further investigated during the course of this paper. Significant differences in properties of the composites are discussed.